Determinants of organizational performance in a reinventing government setting: evidence from the Milwaukee school voucher programme. Issue 10 (26th November 2017) - Ford, Michael R.; Andersson, Fredrik O.
ABSTRACT: This paper advances the institutional entrepreneurial literature by exploring how, and when, the institutional entrepreneurial concepts embedded in theories of Reinventing Government and New Public Management are successful. Specifically, organizational level data from the nation's oldest and largest urban school voucher programme are used to test how fundraising, reliance on government revenue, and membership in an umbrella organization impact different measures of performance. The analysis shows that organizations that fundraise, establish diverse revenue streams, and/or are members of established networks have certain performance advantages. The results are relevant to policymaker considering governance reforms premised on entrepreneurial activity.